High Temperature Oxidation Behavior of Fe-Cr Steel in Air at 1000-1200 K - T. Sudiro; D. Aryanto; A. S. Wismogroho; C Ciswandi; B. Hermanto; H. Izzuddin; R. Pratama (PPIKSN-BATAN, 2018)
The high temperature oxidation behavior of Fe-Cr steel was studied in air at elevated temperatures of 1000, 1100 and 1200 K for up to 72 ks. The mass change of all samples was recorded in order to evaluate their oxidation kinetic. The structure of oxide scales was investigated by mean of X-ray diffraction and SEM-EDX. According to oxidation kinetic curve, the mass gain of oxidized sample increases with increasing oxidation time and temperature. At 1000 and 1100 K, the Fe-Cr steel exhibits an excellent oxidation resistance. As oxidation temperature increase to 1200 K, however, the accelerated oxidation occurred. This is considered due to breakaway oxidation. The Fe-Cr steel forms a duplex oxide layer consisting of Fe-rich oxides in the outer layer and Fe-Cr oxides in the inner layer. The obtained results suggest that the oxidation temperature strongly affects the oxidation resistance of Fe-Cr steel and the structure of formed oxide layer on the steel surface. The influence of oxidation temperature on the oxidation resistance and scale structure is discussed in this paper.